Dinamika Sistem Pemilu dan Demokratisasi Partai Politik di Indonesia Pasca Reformasi - Fatni Erlina (Universitas Muhammadiyah Purwokerto, 2023)
The purpose of writing this article is to find a correlation between the differences in the electoral system adopted and the democratic index of political parties, through a comparative study of changes in the electoral system that have taken place since the Reformation. Election systems can be identified through regulatory changes to the Election Law. The analysis is seen through the perceptions index of Indonesian democracy, namely in the aspects of political institutions, political party variables, and regeneration indicators. This research is descriptive qualitative, using normative juridical analysis methods, and positivist legis. The results showed that differences in the representation system resulted in changes in political party strategy which had implications for internal democratization of political parties. The democracy index of political parties in Indonesia tends to decline after the implementation of an open proportional system and the strengthening of the parliamentary threshold, because political parties are more oriented towards getting votes than regeneration. An alternative that can be done is by combining a proportional electoral system and a district system, a two-chamber parliament system (bicamiral) and accommodating group groups, namely a functional representation system.Keywords: Dynamics, Election System, Democracy, Political Parties